Michelangelo's sculpture : selected essays - Steinberg, Leo, 1920-2011; Schwartz, Sheila (Chicago ; London : The University of Chicago Press, 2018)
Leo Steinberg was one of the most original and daring art historians of the twentieth century, known for taking interpretative risks that challenged the profession by overturning reigning orthodoxies. In essays and lectures that ranged from old masters to contemporary art, he combined scholarly erudition with an eloquent prose that illuminated his subject and a credo that privileged the visual evidence of the image over the literature written about it. His works, sometimes provocative and controversial, remain vital and influential reading. For half a century, Steinberg delved into Michelangelo's work, revealing the symbolic structures underlying the artist's highly charged idiom. This volume of essays and unpublished lectures explicates many of Michelangelo's most celebrated sculptures, applying principles gleaned from long, hard looking.
Introduction / Richard Neer -- The metaphors of love and birth in Michelangelo's Pietàs -- The Roman Pietà: Michelangelo at twenty-three -- Michelangelo's Medici Madonna and related works -- Body and symbol in the Medici Madonna -- Michelangelo's Florentine Pietà: the missing leg twenty years after -- The Michelangelo next door -- Shrinking Michelangelo -- Michelangelo and the doctors -- What would you ask Michelangelo?
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Michelangelo Buonarroti, -- 1475-1564 -- Criticism and interpretation; Michelangelo Buonarroti, -- 1475-1564; Sculpture, Renaissance -- Italy; Sculpture -- Italy -- 16th century; Sculpture -- Italy -- 15th century; Sculpture de la Renaissance -- Italie; Sculpture -- Italie -- 16e siècle.; Sculpture première -- 15e siècle.; ART -- History -- General; Sculpture; Sculpture, Renaissance; Italy; 1400-1599; Christian iconography; Italian Renaissance art; Michelangelo; Sculpture; Criticism, interpretation, etc